Increased resolution can reduce model biases in the Interdecadal Pacific Oscillation - Bo Pang; Riyu Lu; Adam A Scaife; Lin Wang (Environmental Research Letters, 2025)
This study assesses model performance in simulating the Interdecadal Pacific Oscillation (IPO) pattern using the High Resolution Model Intercomparison Project. It is found that models exhibit a large diversity in the western extension of the IPO, leading to distinct global impacts. The IPO-related sea surface temperature (SST) anomalies extend more westward to the equatorial western Pacific (WP) in the low-resolution (LR) models, along with a westward shift of atmospheric responses. However, such biases are largely reduced in the high-resolution (HR) models, ascribing to better behavior in reproducing the mean-state SST in the cold tongue. In general, the HR models simulate smaller zonal advection in the equatorial WP due to a weaker zonal SST gradient compared to the LR models. In addition to the tropics, the intensity of IPO-related SST over the North Pacific is also improved in the HR models due to their benefits in simulating the Kuroshio extension. These findings suggest that the HR models have superior capabilities in predicting and projecting future changes in the IPO.